Two-Photon Fluorescence of Ca2+ Migration in Mice With Vibrating Needle - Xiaoyue Chang; Qihua He; Pui To Lai; Shing Chow Chan; Edward S. Yang (IEEE Photonics Journal)
We report an experiment using a vibrating needle to activate calcium ions and waves in mice muscle tissue fibers. In vivo Ca2+ migration in mice was observed along with its muscle pathways using two-photon laser fluorescence.